The role of tourist reserves in creating an Iraqi model for international communication - M.D. Imran Kazem Al-Karkushi (Peerian Journals Publishing, 2024)
Iraq was known as a historical material due to the accumulation of civilizations and cultures that make up its human, material and cultural existence. According to the civilisational, cultural and geo-political equations, Iraq found itself in a state of internal, regional and international conflict, disputes and competitions that made it a scene of cultural and civilizational destruction that completely took hold of it, and its property and cultural, civilizational and religious heritage were destroyed. Here the following question arises: How can Iraq be protected from the dangers of sustainable international disputes and conflicts? How can its plundered cultural, human and material heritage be restored on planet Earth? How can Iraq be extricated from the clutches of sustained conflict and preserve its history and cultural and human heritage? If Iraq were an international communication protectorate, or a country with multiple protectorates, would it maintain its influence and communication with other civilizations and cultures in a more influential way?
Keywords: communication; protected; civilizations